Influencing Project Design Through Participation : Pakistan Ghazi-Barotha Hydropower Project - World Bank (Washington, DC, 2012)
The Ghazi-Barotha Hydropower Project is a major run-of-river power project designed to meet the acute shortage of power in Pakistan. It is being implemented by the Water and Power Development Authority of Pakistan (WAPDA). The project consists of a barrage located near Ghazi village in the North West Frontier Province, a 52 km long concrete lined power channel and a power complex located near Barotha village in the province of Punjab. It is expected to have an installed capacity of 1450 MW and provide an estimated energy output of 6600 GWh. The project is a major element of the Government's strategy for meeting future power demand in Pakistan. Impacts of the project include changes of land use in areas temporarily and permanently acquired for construction. This will affect about 20,000 people, including resettlement of 179 families with a surveyed population of 899 persons. From the earliest stages of project development, assessment of social impacts was incorporated into the evaluation and selection of alternatives for the siting of major infrastructure components. The analysis of alternatives has allowed for a significant reduction in the extent of resettlement and archeological impacts. The project serves as an example of inclusive project planning. Communities and NGOs worked with social scientists and engineers to develop engineering solutions to mitigate adverse social impacts and to make the project design responsive to social concerns.